Terjadinya Isomerisasi dan Oksidasi - dan -Karoten Selama Proses Pengolahan CPO - Kusumaningtyas, Reni Subawati; Martosupono, artanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
Isomerization and oxidation has been known as the major factors of the degradation of carotenoid compounds.The carotenoid compounds in oil palm fruit are dominated by - and -karoten. Result of this experiment showedthat the isomerization of the - and -karoten during the process productions of crude palm oil (CPO) indicated bythe reducing of trans ? and trans -caroten concentrations and followed by the increasing of cis - and cis ?-caroten concentrations. Isomerization promote to increasing the concentration of cis - and cis -carotenapproximately 40 ppm and 19 ppm on the sterilization process, then 79 ppm and 134 ppm on the extraction andclarification process of crude oil. On the other hand, the purification process just only increased the concentrationof cis ?-karoten about 19 ppm. The Oxidation of the - and -caroten caused to the increasing of lutein andzeaxantin as the degradation product. The - and -caroten oxidation can be increasing the amount of lutein andzeaxantin approximately 1 ppm and 5 ppm on the sterile fruit, 22 ppm and 14 ppm on the extract crude oil, 1 ppmand 3 ppm on purifying oil. The oxidation process of oil palm extract in the vacuum drier tank can be increased thelutein concentration about 6 ppm.